Model Discovery Learning Untuk Meningkatkan Hasil Belajar Pak Materi Hidup Dalam Roh Kudus Fase C Kelas V SD Negeri Magelang 6 - Dian Anom Sari; Hartutik Hartutik; Paulus Asriadi (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Concern about student learning outcomes in affective and cognitive aspects is urgent in efforts to raise a young generation with noble and religious morals. The problem of low learning outcomes in Catholic Religious Education which has not yet reached the target of student learning completeness and low moral aspects in humans is a concern. This research was designed to overcome this problem by applying the Discovery Learning learning model. This model emphasizes the active role of students in learning, with the teacher acting as a facilitator. The aim of this research is to improve student learning outcomes in affective aspects, especially morals, and cognitive aspects. This research is classroom action research designed in two cycles, with data collection through observation, interviews, documentation and tests. Indicators of observing morals in humans include 1) Identifying similarities with other people; 2) Make it happen in group activities; 3) Recognize various possible interpretations; 4) Viewing things from other people's perspectives; 5) Identify the goodness and strengths of the people around you. The achievement targets in this research are: 10% Developing According to Expectations and 90% Very Developing. Meanwhile, the cognitive aspect assessment achievement indicators include 90-100 = Proficient, 80-89 = Proficient, 65-79 = Adequate, 0-64 = Medium, with an achievement target of 10% Adequate, 90% Proficient. The results of the research show that the Discovery Learning Model in Catholic Religious Education learning is proven to be able to increase the dimensions of faith, devotion to God Almighty, and noble character in the matter of living in the Holy Spirit, namely from cycle 1 to 2 by 28% and the target achievement and learning achievement values ​​of students in cycle I from 75% adequate, 25% proficient, 0% proficient in cycle II to 75% proficient and 25% proficient. Finally, this research suggests using the Discovery Learning model as an effort to improve the Pancasila Student Profile in the learning process.